CSIG-09. THERAPEUTIC TARGETING OF PRENATAL PONTINE ID1 SIGNALING IN DIFFUSE MIDLINE GLIOMA. (14th November 2022) - Messinger, Dana; Harris, Micah; Cummings, Jessica; Thomas, Chase; Yang, Tao; Sweha, Stefan; Woo, Rinette; Siddaway, Robert; Burkert, Martin; Stallard, Stefanie; Qin, Tingting; Mullan, Brendan; et al.
Abstract: Diffuse midline gliomas (DMG) are highly invasive brain tumors with rare survival beyond two years past diagnosis. The mechanism behind tumor invasion is currently not well understood. Previous reports demonstrate upregulation of the protein ID1 with H3K27M and ACVR1 mutations in DMG, but this has not been confirmed in human tumors or therapeutically targeted. Whole exome, RNA, and ChIP-sequencing were performed on the ID1 locus in DMG tissue. Scratch-assay migration and transwell invasion assays of cultured cells were performed following shRNA-mediated ID1-knockdown. In vitro and in vivo genetic and pharmacologic [cannabidiol (CBD)] inhibition of ID1 on DMG tumor growth was assessed. Additional in vitro experiments were performed to determine a potential mechanism of action for CBD-mediated effects. Self-reported CBD dosing information was collected from DMG patients. We found that increased ID1 expression in human DMG and in utero electroporation (IUE) murine tumors is associated with H3K27M mutation and brainstem location. ChIP-sequencing indicates a similar epigenetically active state at ID1 regulatory regions in human H3K27M-DMG tumors and prenatal pontine cells. Higher ID1-expressing astrocyte-like DMG cells share a transcriptional program with oligo/astrocyte-precursor cells (OAPCs) from the developing human brain and demonstrate upregulation of the migration regulatory protein SPARCL1. Genetic and pharmacologic (CBD) suppression of ID1 decreases tumor cell migration, tumor growth, and to a lesser extent invasion in both murine IUE and multiple patient-derived in vivo DMG models, improving mouse survival. ID1 knockdown significantly decreases the effect of CBD on migration, tumor growth, and invasion. CBD increases reactive oxygen species production, which also affects DMG cell proliferation in a non-ID1 mediated manner. Overall, we find that H3K27M-mediated reactivation of ID1 in DMG results in a SPARCL1+ migratory transcriptional program that is therapeutically targetable with CBD.